THE INFLUENCE OF ORGANIZATIONAL CULTURE AND THE WORK ENVIRONMENT ON EMPLOYEE WORK SPIRIT IN THE COMMUNICATION DEPARTMENT, INFORMATION AND CODE OF KAMPAR DISTRICT - Meldo, Yogi Andrean; Zulher, Zulher; Setiawan, Adi (Jurnal Riset Manajemen Indonesia, 2021)
This study aims to determine the influence of organizational culture and work environment on employee morale at the Department of Communication, Information and Encoding, Kampar Regency. The population in this study were all employees at the Kampar Regency Communication, Information and Encryption Service using census techniques in determining the sample to be 33 employees. The data collection techniques used were questionnaires and research files. The data analysis technique used is multiple linear regression analysis with a significant level (α) of 0.05. The results of this study concluded that the work environment has a significant partial effect on employee morale, with a significant value greater than 0.05. The results of the analysis of this study indicate that organizational culture and work environment influence the morale of employees at the Department of Communication, Information and Encryption, Kampar Regency. There is a very strong relationship between the variables of organizational culture and work environment on employee morale at the Communication, Information and Encryption Office of Kampar Regency.